2020
DOI: 10.3390/genes11030271
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Selected miRNA in Uveal Melanoma Primary Tumors as Early Biomarkers of Disease Progression

Abstract: Uveal melanoma (UM) is the most common primary tumor of the eye diagnosed in adults, associated with a high risk of metastasis and thereby, poor prognosis. Among known risk factors for the development of metastatic disease is the loss of BAP1 expression and chromosome 3 monosomy in the primary tumor. However, the expression levels of specific micro RNAs (miRNA) in tumor tissue may also serve as a valuable marker for determining the risk of metastatic disease in patients with primary uveal melanoma. In our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…They identified a panel of 15 miRNAs differentially expressed between four TCGA-UM study patients (stage IIA tumours and without metastatic disease) and four TCGA-UM patients (stage IV with metastatic disease). Further validation of six of the miRNAs in 28 primary UM with no evidence of metastasis and 18 primary UM, where metastatic disease had developed at the time of follow-up, demonstrated that miR-592, miR-346 and miR-1247 were significantly increased, and that miR-506 and miR-513c were significantly decreased in the metastatic subgroup [80].…”
Section: Mirna Expression and Metastatic Risk In Ummentioning
confidence: 98%
See 1 more Smart Citation
“…They identified a panel of 15 miRNAs differentially expressed between four TCGA-UM study patients (stage IIA tumours and without metastatic disease) and four TCGA-UM patients (stage IV with metastatic disease). Further validation of six of the miRNAs in 28 primary UM with no evidence of metastasis and 18 primary UM, where metastatic disease had developed at the time of follow-up, demonstrated that miR-592, miR-346 and miR-1247 were significantly increased, and that miR-506 and miR-513c were significantly decreased in the metastatic subgroup [80].…”
Section: Mirna Expression and Metastatic Risk In Ummentioning
confidence: 98%
“…A similar approach was taken by Wróblewska et al, but this time combining TCGA miRNA data with miRNA validation in patient samples [80]. They identified a panel of 15 miRNAs differentially expressed between four TCGA-UM study patients (stage IIA tumours and without metastatic disease) and four TCGA-UM patients (stage IV with metastatic disease).…”
Section: Mirna Expression and Metastatic Risk In Ummentioning
confidence: 99%
“…In our previous study, we reported the possible use of miRNAs differentially expressed in UM tumours as biomarkers for the assessment of metastatic risk in uveal melanoma patients [69]. In this study, we present the first analysis of inflammatory-related protein cargo of exosomes derived from the serum of healthy donors and uveal melanoma patients with primary and metastatic disease.…”
Section: Discussionmentioning
confidence: 96%
“…Results corresponded to either elevated (miR-592, miR-346, and miR-1247) or decreased (miR-506 and miR-513c) expression in the metastatic stage. miR-196b did not show quantitative differences in its expression, but was correlated with the expression of BAP1 [ 65 ]. In histological samples, Radhakrishnan and coworkers related chromosomal alterations of pairs 1, 3, and 8 with miRNA expression according to whether the samples belonged to tumors that had developed liver metastases or not [ 66 ].…”
Section: Micrornas In Ummentioning
confidence: 99%